Association between hepatic oxygenation on near-infrared spectroscopy and clinical factors in patients undergoing hemodialysis. - Yuichiro Ueda; Susumu Ookawara; Kiyonori Ito; Yusuke Sasabuchi; Hideyuki Hayasaka; Masaya Kofuji; Takayuki Uchida; Sojiro Imai; Satoshi Kiryu; Saori Minato; Haruhisa Miyazawa; Hidenori Sanayama; et al. (PLoS ONE, 2021)
The hepato-splanchnic circulation directly influences oxygenation of the abdominal organs and plays an important role in compensating for the blood volume reduction that occurs in the central circulation during hemodialysis (HD) with ultrafiltration. However, the hepato-splanchnic circulation and oxygenation cannot be easily evaluated in the clinical setting of HD therapy. We included 185 HD patients and 15 healthy volunteers as the control group in this study. Before HD, hepatic regional oxygen saturation (rSO2), a marker of hepatic oxygenation reflecting the hepato-splanchnic circulation and oxygenation, was monitored using an INVOS 5100c oxygen saturation monitor. Hepatic rSO2 was significantly lower in patients undergoing HD than in healthy controls (56.4 ± 14.9% vs. 76.2 ± 9.6%, p < 0.001). Multivariable regression analysis showed that hepatic rSO2 was independently associated with body mass index (BMI; standardized coefficient: 0.294), hemoglobin (Hb) level (standardized coefficient: 0.294), a history of cardiovascular disease (standardized coefficient: -0.157), mean blood pressure (BP; standardized coefficient: 0.154), and serum albumin concentration (standardized coefficient: 0.150) in Model 1 via a simple linear regression analysis. In Model 2 using the colloid osmotic pressure (COP) in place of serum albumin concentration, the COP (standardized coefficient: 0.134) was also identified as affecting hepatic rSO2. Basal hepatic oxygenation before HD might be affected by BMI, Hb levels, a history of cardiovascular disease, mean BP, serum albumin concentration, and the COP. Further prospective studies are needed to clarify whether changes in these parameters, including during HD, affect the hepato-splanchnic circulation and oxygenation in HD patients.